KONDISI EKONOMI PETANI DALAM KONFLIK AGRARIA(STUDI PADA ANGGOTA SERIKAT PETANI INDONESIA) - Sinaga, Randa Putra Kasea; Adi, Isbandi Rukminto (UI Scholars Hub, 2020)
Various problems faced by peasants have caused the decreasing of peasants population in Indonesia. One of those problems is agrarian conflict. For instance, agrarian conflicts which are being faced by SPI (Indonesian Peasant Union) Villages Mekar Jaya and Simpang Sei Kopas bases peasant members, which are object of this research. The objective of this research are to elaborate and analyze the economic condition of peasants in agrarian conflicts situation both before and after organizing social action. Based on observation and in-depth interview with informants, it has been known that economic condition of peasant will be better when peasants control the conflicting land that had been previously converted to agricultural land by peasants, in compared when peasants are not controlling the land or experiencing land clearing. This research conclusion is that situation of land controlling over land conflict becomes determinant factor for economic condition of peasants.